Analisis Pengaruh Penyebab Change order pada Pembangunan Apartemen di Kota Surabaya (Universitas 17 Agustus 1945 Surabaya, 2023)
The main objective of construction projects is to achieve the desired outcome, which means that the final results should align with the project plan and contract agreement. However, construction projects often encounter problems such as changes in orders. These changes can be caused by a variety of factors, including the decision of the owner, environmental, consultants, and other variables. The purpose of this study was to identify the causes of order changes, the most significant cause of order changes, and the extent to which order changes impact the development of apartments in Surabaya. The research methodology used in this study was descriptive statistic analysis, and the data was collected through questionnaires administered to the contractor management teams working on the Bess Mansion construction projects. The results revealed that there were 24 and 22 variables, respectively, that were identified as causes of order changes. The project owner was found to have the most significant impact on quality, accounting for 52.90% of the changes. The impact of order changes for the Bess Mansion Apartment construction project.